Protein energy requirements under conditions prevailing in developing countries current knowledge and research needs (Food and nutrition bulletin / Suppl., 1979)
Abstract: The determination of protein and energy needs in developing nations is complicated by insufficient data, degree of social stress, presence of disease and infection, and differences of individuals and population. An attempt is being made, however, to define the necessary allowances for recovery from infection or mild malnutrition and for the maintenance of health. The crucial questions revolve around relative requirements under prevailing conditions, whether there are indeed different requirements for different populations, and whether those requirements can be determined in reference to healthy, will-fed populations. These questions are addressed through information on known protein and energy requirements for health maintenance and tissue repletion, and nutritional consequences of infections. Recommendations are outlined for research priorities.